Human CARD9: A Critical Molecule of Fungal Immune Surveillance - Drummond, Rebecca A.; Franco, Luis M.; Lionakis, Michail S. (Frontiers in Immunology, 2018)
CARD9 is a signaling adaptor protein that is involved in the transduction of signals from a variety of innate pattern recognition receptors, including the C-type lectin receptors and intracellular NOD receptors and nucleic acid sensors. As a result, CARD9 has been shown in animal models to be an important regulator of immunity to bacteria, fungi and viruses. Studies in humans with autosomal recessive CARD9 deficiency have indicated a highly specific role for this molecule in the activation of antifungal immune responses in the central nervous system, the oral mucosa and the skin. Moreover, CARD9-dependent functions have recently been indicated to modulate the development of autoimmunity, inflammatory bowel diseases and cancer. In this mini-review, we highlight the recent studies that have identified several novel functions of CARD9 in various disease contexts, and we summarize the contemporary understanding of the genetics and immunology of human CARD9 deficiency.